Retrospective Evaluation of Relationship Between Iron Overload and Transplantation Complications in Pediatric Patient Who Underwent Allogeneic Stem Cell Transplantation Due to Acute Leukemia and Myelodysplastic Syndrome - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2020)
Background:Hematopoietic stem cell transplantation (HSCT) is a curative therapy option for hematologic malignancies. Iron overload is common in this patient group and can impact short-term and long-term nonrelapse mortality.Study Design:Retrospective observational cohort study.Aims:To evaluate the effect of iron load on early and late HSCT outcomes in patients with acute leukemia and myelodysplasia to assess the necessity of reducing iron load.Patients and Methods:Sixty patients who underwent HSCT in pediatric stem cell transplantation unit between 2000 and 2012 were evaluated retrospectively. The patients were divided into those with pretransplantation serum ferritin levels above and below the median value of 1299ng/mL.Results:Forty-two (70%) of the patients were male, mean ages of the low and high ferritin groups were 85.439.42 and 118.56 +/- 10.04 months, respectively. Acute graft-versus-host disease (GVHD) within the first 100 days and acute liver GVHD were significantly more common in the high ferritin group (P<0.011 for both). Ferritin level was not associated with rates of engraftment syndrome, veno-occlusive disease, early/late infection, relapse, or overall and disease-free survival.Conclusions:In our study, significant result especially in terms of acute liver GVHD, was important to emphasize the need to be more careful in terms of acute liver GVHD risk in early liver pathologies in patients with high levels of ferritin after transplantation. In future large studies may be helpful to explain the relationship between acute liver GVHD and high ferritin levels.
Keywords: pediatric patient; allogeneic hematopoietic stem cell transplantation; ferritin; graft-versus-host disease; iron overload; survival; BONE-MARROW-TRANSPLANTATION; PRETRANSPLANTATION SERUM FERRITIN; VERSUS-HOST-DISEASE; PROGNOSTIC IMPACT; NONRELAPSE MORTALITY; RISK-FACTOR; LIVER; HYPERFERRITINEMIA; TRANSFUSIONS; THALASSEMIA